2011
DOI: 10.1002/cncr.26045
|View full text |Cite
|
Sign up to set email alerts
|

Oncofertility and preservation of reproductive capacity in children and young adults

Abstract: With increasing numbers of survivors from cancer at a young age, the issue of fertility preservation has assumed greater importance. This review describes normal ovarian and testicular function and summarizes what is known about the effect of chemotherapy and radiotherapy on the gonads and uterus. All young patients with cancer or leukemia should have their fertility prognosis discussed before the initiation of treatment. Sperm and embryo cryopreservation should be considered standard practice and be widely av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(122 citation statements)
references
References 54 publications
2
114
0
5
Order By: Relevance
“…16,52,[101][102][103][104][105] The ASCO Clinical Practice Guidelines recommend that providers discuss the options for fertility preservation with all new patients with cancer at diagnosis. 106 Nevertheless, fertility preservation is currently one of the most underprescribed and least implemented services in AYA patients with cancer.…”
Section: Fertility Preservationmentioning
confidence: 99%
See 2 more Smart Citations
“…16,52,[101][102][103][104][105] The ASCO Clinical Practice Guidelines recommend that providers discuss the options for fertility preservation with all new patients with cancer at diagnosis. 106 Nevertheless, fertility preservation is currently one of the most underprescribed and least implemented services in AYA patients with cancer.…”
Section: Fertility Preservationmentioning
confidence: 99%
“…106 Nevertheless, fertility preservation is currently one of the most underprescribed and least implemented services in AYA patients with cancer. 52,101,107 A study that reviewed 231 records of AYA patients with leukemia/lymphoma, sarcoma, or breast or testicular cancers showed that infertility risk was discussed 26% of the time and fertility preservation options were discussed 24% of the time. 108 However, it is possible that more discussions about infertility occurred without having been documented.…”
Section: Fertility Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Childhood Cancer Survivor Study indicated that male survivors were substantially less likely to attain a pregnancy (hazard ratio 0.56, 95% CI 0.49-0.63) compared to their siblings (Green et al 2010). Nevertheless, although male infertility is one of the major lateterm concerns of anti-cancer treatments during childhood and adolescence (Brougham et al 2003, Wallace 2011, the mechanism of chemotherapy-induced testicular toxicity remains to be elucidated. Studies have demonstrated that several classes of chemotherapy alter spermatogenesis in the pre-pubertal and early pubertal testis (Masala et al 1997, Thomson et al 2002, Longhi et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…This has generated new expectations especially for women of adolescent and reproductive age for whom an increased hope of recovery from disease implies a prospect of parenthood [2]. Unfortunately, radioand chemotherapies have major effects on ovarian function, often leading to premature ovarian failure.…”
Section: Introductionmentioning
confidence: 99%